2019
DOI: 10.1007/s13197-019-03923-2
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of corn germ oil with supercritical CO2 and cosolvents

Abstract: The aim of this work was to investigate corn germ oil extraction using supercritical CO 2 and cosolvents addition (hexane, acetone and ethanol). The effects of temperature (45-85 °C) and pressure (15-25 MPa) on the extract yield were evaluated for the tests conducted only with supercritical CO 2 . The addition of cosolvents to supercritical CO 2 was also examined at 25 MPa and 60 °C.The conventional Soxhlet extraction with different organic solvents was also performed for comparison purposes. The results of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Solvent extraction, one of the most common methods, yields crude oil that often requires refining to enhance the quality of the extracted TA B L E 1 Summary of corn oil extraction methods. [15][16][17][18][19] Although mechanical pressing is favored for its simplicity and preservation of natural properties, solvent extraction is often chosen for its higher efficiency, especially in large-scale industrial processes.…”
Section: Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvent extraction, one of the most common methods, yields crude oil that often requires refining to enhance the quality of the extracted TA B L E 1 Summary of corn oil extraction methods. [15][16][17][18][19] Although mechanical pressing is favored for its simplicity and preservation of natural properties, solvent extraction is often chosen for its higher efficiency, especially in large-scale industrial processes.…”
Section: Processingmentioning
confidence: 99%
“…[29] An emerging technology is the use of supercritical CO 2 extraction. [17] This method involves adjusting influencing factors in the extraction process using CO 2 in a supercritical state, leading to improved extraction efficiency and better quality corn germ oil.…”
Section: Extractionmentioning
confidence: 99%
“…The use of co-solvent was found to be advantageous for some raw materials. [70,71] For crambe seed oil, use of propane increased the overall oil yield. The subsequent thermal treatment also increased the stability of oils.…”
Section: Supercritical Carbon Dioxide Extraction Of Oils Rich In Poly...mentioning
confidence: 99%
“…The solvation characteristics of ScCO 2 can be altered by adding chemical entertainers such as ethanol, acetone, methanol, and isopropanol, which interact with the solute and enhance solubility (Wejnerowska & Ciaciuch, 2018). Marinho et al (2019) reported that extraction of corn germ oil by the addition of co‐solvents (ethanol, hexane, and acetone) to ScCO 2 at 25 Mpa and 60°C facilitated higher yield, with maximum yield using ethanol as cosolvent (13.81%). Nimet et al (2011) investigated the sunflower oil extraction using ScCO 2 and subcritical propane and concluded that under all conditions liquid propane gave higher oil yield at low pressure.…”
Section: Oil Extraction Technologiesmentioning
confidence: 99%